Analysis of RBS Chrome's Employee Preparedness Conditions Against Fire Threats - Listyaningsih, Diah; Rossa, Wanda Virna; Aulady, Mohammad F.N (Faculty of Civil Engeneering and Planning - ITATS, 2022)
Fire is an event where a fire is not where it should be, resulting in material or life losses that can occur anywhere. Fatal fires are those that occur in the industrial sector because they will disrupt operational and production activities. The purpose of this study is to analyze employee preparedness for facilities or infrastructure from the protection system in RBS CHROME and find out the comparison of the preparedness of production employees and management employees to fire hazards in RBS CHROME. This type of research is descriptive quantitative. The design of this study used a list of questions as a guideline for interviews and field observations. The list of questions to informants of the study was carried out on 3 groups of employees, namely production employees and management employees of RBS CHROME. Field observation of facilities or infrastructure using a checklist sheet that refers to a ministerial regulation. The results of this study show that RBS CHROME has provided facilities or facilities for fire disaster preparedness, but employees who are in the RBS CHROME office do not understand and are not prepared for fire disasters